1997
DOI: 10.1086/262070
|View full text |Cite
|
Sign up to set email alerts
|

Collective Labor Supply and Household Production

Abstract: This paper emphasises the importance of incorporating household production into the 'collective model' of the household, and considers how

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(131 citation statements)
references
References 3 publications
1
122
0
8
Order By: Relevance
“…The underlying notion of the empirical analysis below is basically in line with an extension of Chiappori (1992), Apps and Rees (1997), which utilizes the crucial insight that time not spent in market labor supply is used for both household production as well as for pure leisure. The idea of this distinction came up first by Mincer (1962), at least for the case of women, and later by Becker (1965) and Gronau (1977).…”
Section: Theory and Literaturementioning
confidence: 99%
“…The underlying notion of the empirical analysis below is basically in line with an extension of Chiappori (1992), Apps and Rees (1997), which utilizes the crucial insight that time not spent in market labor supply is used for both household production as well as for pure leisure. The idea of this distinction came up first by Mincer (1962), at least for the case of women, and later by Becker (1965) and Gronau (1977).…”
Section: Theory and Literaturementioning
confidence: 99%
“…One of the most serious deficiencies of this model concerns the treatment of domestic production: housework is ignored so that non-market time coincides with pure leisure. Apps and Rees (1997) rightly point out that, in that case, a low level of market labor supply is automatically interpreted as greater consumption of leisure, whereas it may in fact reflect the specialization of one of the members in home production.…”
Section: Introductionmentioning
confidence: 99%
“…This is a serious problem which is tackled by Apps and Rees (1997) and Chiappori (1997). In particular, the latter author considers a collective model of domestic and market labor supplies with marketable domestic production.…”
Section: Introductionmentioning
confidence: 99%
“…If we would observe that she receives more goods than we would predict, then we could attribute the observation to her having a high taste for goods relative to leisure. 2 If, on the other hand, we observed that she also receives less goods then it looks as though she lacks 'power'within the household and that the distribution of material well-being within the household is skewed towards the husband. Clearly, we need to observe both sets of outcomes (the allocation of time and money) to calculate the intra-household distribution of material well-being and its determinants.…”
Section: Introductionmentioning
confidence: 79%